Continuous Use of Tribenuron-Methyl Selected for Cross-Resistance to Acetolactate Synthase–inhibiting Herbicides in Wild Mustard (Sinapis arvensis). Issue 4 (23rd July 2018) - Gherekhloo, Javid; Hatami, Zahra M.; Alcántara-de la Cruz, Ricardo; Sadeghipour, Hamid R.; De Prado, Rafael
Abstract: Wild mustard ( Sinapis arvensis L.) is a weed that frequently infests winter wheat ( Triticum aestivum L.) fields in Golestan province, Iran. Tribenuron-methyl (TM) has been used recurrently to control this species, thus selecting for resistant S. arvensis populations. The objectives were: (1) to determine the resistance level to TM of 14 putatively resistant (PR) S. arvensis populations, collected from winter wheat fields in Golestan province, Iran, in comparison to one susceptible (S) population; and (2) to characterize the resistance mechanisms and the potential evolution of cross-resistance to other classes of acetolactate synthase (ALS)-inhibiting herbicides in three populations (AL-3, G-5, and Ag-Sr) confirmed as being resistant (R) to TM. The TM doses required to reduce the dry weight of the PR populations by 50% were between 2.2 and 16.8 times higher than those needed for S plants. The ALS enzyme activity assays revealed that the AL-3, G-5, and Ag-Sr populations evolved cross-resistance to the candidate ALS-inhibiting herbicides from the sulfonylureas (SU), triazolopyrimidines (TP), pyrimidinyl-thiobenzoates (PTB), sulfonyl-aminocarbonyl-triazolinone (SCT), and imidazolinones (IMI) classes. No differences in absorption, translocation, or metabolism of [ 14 C]TM between R and S plants were observed, suggesting that these non-target mechanisms were not responsible for the resistance. The ALS gene of the R populations contained the Trp-574-Leu mutation, conferring cross-resistance to the SU, SCT, PTB, TP, and IMI classes. The Trp-574-Leu mutation in the ALS gene conferred cross-resistance to ALS-inhibiting herbicides in S. arvensis from winter wheat fields in Golestan province. This is the first TM resistance case confirmed in this species in Iran.